Peningkatan Program Bina Pribadi Islam di SMA Islam Terpadu Granada Samarinda - Muhammad Hendrie Fauzan (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2020)
In this era, there are changes in the behavior of the younger generation. Many students are engaging in promiscuity, smoking, consuming alcoholic, bullying, and using prohibited drugs. School efforts are needed to changes these negative behavioral. One of effort is through the Islamic personal development program. This Islamic development program emphasizes on Nurturing. Development, etymologically derived from the Arabic language "bana" it is means to nurture, build, or establish. This program is specifically focused on Islamic development because an Islamic personality cannot be inherited and is not formed instantly, but it's something that needs to be built, cultivated continuously day by day through thoughts and actions, thought by thought, action by action.